2013
DOI: 10.1016/j.jadohealth.2012.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Ambivalent Messages: Adolescents’ Perspectives on Pregnancy and Birth

Abstract: Abstract:Purpose To examine, from a youth's perspective, adolescent pregnancy and parenting in Baltimore, Maryland, a city with high rates of adolescent pregnancy. MethodsSix gender-stratified focus groups with 13-to 19-year-olds (4 female and 2 male groups; n = 47). We recorded focus groups, transcribed them verbatim, and analyzed them using the constant comparison method. Participants completed questionnaires to collect demographic and behavioral information. ResultsResults fit into a social-ecological frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 22 publications
4
19
0
Order By: Relevance
“…The context from which early adolescent never-pregnant females view adolescent pregnancy is heavily intertwined with their desire for parental approval, academic/athletic achievement, and peer acceptance. This is consistent with previous literature (Kogan et al, 2013; Tanner et al, 2013). However, findings underscore the emotional struggles of early adolescents as they try to give meaning to the potential impact pregnancy would have on their lives.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The context from which early adolescent never-pregnant females view adolescent pregnancy is heavily intertwined with their desire for parental approval, academic/athletic achievement, and peer acceptance. This is consistent with previous literature (Kogan et al, 2013; Tanner et al, 2013). However, findings underscore the emotional struggles of early adolescents as they try to give meaning to the potential impact pregnancy would have on their lives.…”
Section: Discussionsupporting
confidence: 94%
“…Questions outlined in the interview guide explored these factors as they related to adolescents females’ perceptions of adolescent pregnancy and how becoming pregnant as an adolescent would impact their lives. In this study, the concepts identified in the integrated conceptual framework were selected based on findings from other studies focused on adolescent pregnancy and sexual risk reduction that examined factors that influence and predict sexual behavior (Buhi & Goodson, 2007; Kogan et al, 2013; Mollborn, 2010; Tanner et al, 2013). …”
Section: Methodsmentioning
confidence: 99%
“…The study results are consistent with previous work that has framed adolescent pregnancy as a multi-systemic, multi-level issue (Catania & Dolcini, 2012;Cavazos-Rehg et al, 2010;Pedrosa, Pires, Carvalho, Canavarro, & Dattilio, 2011). The different social-ecological influences in Baltimore that affect adolescent pregnancy underscore the importance of considering the larger social context of adolescents' lives (Tanner et al, 2013). Geographical mapping is a tool that can support understanding of the contextual variables (e.g., poverty) related to adolescent pregnancy (Blake & Bentov, 2001;Kegler, Rodine, Marshall, Oman, & McLeroy, 2003).…”
Section: Discussionsupporting
confidence: 88%
“…Research on adolescent pregnancy has focused on incidence and prevalence rates, factors associated with teen pregnancy, the structure of adolescent mother's family of origin, and the effectiveness of pregnancy prevention programs (Dogan-Ateş & Carrión-Basham, 2007;Erdmans & Black, 2008;Hoffman & Maynard, 2008;Mercer, 1981Mercer, , 1985SmithBattle, 1995SmithBattle, , 2007Tanner et al, 2013). Researchers have also studied teen pregnancy as a phenomenon linked to individual behaviors and risk-taking lifestyle choices (Breheny & Stephens, 2010).…”
Section: Study Design and Methodsmentioning
confidence: 99%